Phenytoin Induced Steven Johnson Syndrome: A Case Report - Inamdar, Syed Zia; Chirasani, Swapnapriya; Janagond, Ajit; Londhe, Sushilkumar; Katragadda, Pradeepthi; Paramagond, Mallinath; Kulkarni, Raghavendra Vinayakarao; Naikwadi, Akram; Khot, Anant; Patil, Arvind (Indian Journal of Pharmacy Practice)
Stevens-Johnson syndrome (SJS) is a disastrous consequence of hypersensitivity reaction precipitated by certain drugs and viral infections. It is an idiosyncratic drug reaction usually associated with drugs like anti-epileptics, non-steroidal anti-inflammatory compounds and antibiotics. The syndrome is characterized by purpuric macules and bullous eruptions involving the mucous membrane which may be followed by systemic manifestations. We report here a case of phenytoin induced SJS, the clinical features of this condition and management of the patient are described in brief. The Naranjo adverse drug reaction causality assessment yielded “probable” causal association between the suspected drug and the adverse drug reaction and severity of the reaction was found to be of “moderately” severe in nature.
Keywords: Adverse Drug Reaction; Phenytoin; Steven Johnson Syndrome; Antiepileptics Naranjo; Idiosyncratic Drug Reaction; Toxic Epidermal Necrolysis